Diverticulosis, Adenomas, and Cancer in the Colon: A Systematic Review and Meta-Analysis of Endoscopic Studies - Del Forno, Alessandro; Zullo, Angelo; Marmo, Clelia; Marmo, Riccardo; Manta, Raffaele; De Francesco, Vincenzo; Fiorini, Giulia; Pavoni, Matteo; Vaira, Dino (Journal of clinical gastroenterology, 2024)
To perform a systematic review and meta-analysis of endoscopic studies to evaluate an association between diverticulosis and neoplastic lesions in the colon. Some epidemiological observations suggest an association between diverticulosis and adenoma/cancer in the colon. However, an increased risk of colon neoplastic lesions in diverticulosis subjects was found to be increased in some studies, but not in others, puzzling data interpretation. From the retrieved studies, prevalence of adenomas, advanced adenomas, cancer or neoplasia (advanced adenoma or cancer) was compared between subjects with or without diverticulosis, and comparisons in subgroups were also performed. Data of 26 studies with a total of 419,623 patients were eventually considered, including 27,092 patients with diverticulosis. Data analysis found a statistically significant association between diverticulosis and adenomas (OR: 1.88; 95% CI: 1.50-2.25), advanced adenomas (OR: 1.49; 95% CI: 1.02-2.16), and neoplasia (OR: 1.50; 95% CI: 1.11-2.02), but not with cancer alone (OR: 1.01; 95% CI: 0.70-1.47). These associations were confirmed in the subgroup analyses, by considering Caucasian and Asian populations, prospective and retrospective studies, screening or symptoms settings, and between good or fair quality studies. A statistically significant association between diverticulosis and adenomas, advanced adenomas and neoplasia, but not with cancer alone was found. However, the strength of association seems to be insufficient to impact on clinical practice.